Peranan Pengaplikasian Fitur “Guarantor Account” di Website E-Visa Imigrasi Indonesia Terhadap Ekstensi Visa di Kantor Imigrasi Kelas I TPI Denpasar - Saputra, I Made Dedi Ari; Prabawati, Ni Putu Anik (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The influence of the massive technology and information in the current era has touched various types of existing fields, even entering the realm of government agencies. The Class I TPI Denpasar Immigration Office is one of the government agencies that has implemented an understanding of e-government into its service sector, namely the application of the “Guarantor Account” feature on the Indonesian Immigration e-Visa site to facilitate the visa extension process for Foreign Citizens (WNA) who live in the work area of the Class I TPI Denpasar Immigration Office. This study aims to see and find out how far the role of the application of this feature is in the existing visa extension process. This study uses a descriptive qualitative approach to find out data and information in depth. The data collection process is carried out through 3 main methods, namely through observation, documentation stage, and also interviews with related sources. The results of the study provide information that the implementation of the “Guarantor Account” feature has a positive impact in the form of convenience felt by applicants for visa extensions for Limited Stay Permit Cards (KITAS) Permanent Stay Permit Cards (KITAP) but is also accompanied by a negative impact in the form of a high risk of data falsification. However, this has been anticipated by the immigration agency by requiring visa extension applicants to verify their files by coming directly to the Class I TPI Denpasar Immigration Office. The implementation of this regulation certainly has a significant positive impact on the level of security of Indonesian visa ownership.